A new derivatization method for the determination of propineb in black tea and infant formula samples using dispersive liquid-liquid microextraction followed by gas chromatography-mass spectrometry - Bodur, Suleyman; Erarpat, Sezin; Gunkara, Omer Tahir; Chormey, Dotse Selali; Bakirdere, Sezgin (ELSEVIER, 2020)
A novel derivatization method for the determination of propineb by gas chromatography-mass spectrometry (GC-MS) was developed in this study. This was achieved by isothiocyanate derivatization of the analyte by potassium persulfate and potassium carbonate in water medium. Dispersive liquid-liquid microextraction (DLLME) was employed to isolate and preconcentrate the derivatized analyte into an organic phase. All method parameters including concentration/volume of potassium persulfate and potassium carbonate salts, type/period of mixing for derivatization reaction and microextraction process were systematically optimized to lower the detection limit. Under the optimum experimental conditions, the limit of detection (LOD) and limit of quantitation (LOQ) values were calculated as 0.15 mg/kg and 0.52 mg/kg, respectively. The developed method was checked for its accuracy and applicability by spiking black tea and infant formula samples, and the respective percent recovery results were found to be in the range of 99-102% and 98-103%, respectively.
Keywords: Propineb; Isothiocyanate derivatization; DLLME; GC-MS; DITHIOCARBAMATE; VALIDATION; RESIDUES; Chemistry